The Chain Mediating Role of Hope and Posttraumatic Growth Between Social Support and Psychological Distress Among Lung Cancer Patients - Huang JG; Xu CH; Shi YM; Jiang J; Huang FM; Xu LL (Cancer Management and Research)
Jin-Gui Huang,1,* Chen-Han Xu,2,* Yu-Mei Shi,1 Juan Jiang,3 Feng-Mei Huang,1 Ling-Li Xu4 1Department of Medical Oncology, Chongqing University Cancer Hospital, Chongqing, 400030, People’s Republic of China; 2College of Computer Science, Chongqing University, Chongqing, 400000, People’s Republic of China; 3Department of Gastroenterology, Chongqing University Cancer Hospital, Chongqing, 400030, People’s Republic of China; 4Department of Human Resources, Chongqing University Cancer Hospital, Chongqing, 400030, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ling-Li Xu, Department of Human Resources, Chongqing University Cancer Hospital, No. 181, Hanyu Street, Shapingba District, Chongqing, 400030, People’s Republic of China, Tel +86 15823276672, Email 15823276672@163.comPurpose: This research was designed to explore whether hope and posttraumatic growth (PTG) played a mediating role between social support and psychological distress in patients diagnosed with lung cancer.Patients and Methods: A hospital-based cross-sectional study was carried out on 502 lung cancer patients. From September 2023 to April 2024, participants were recruited via convenience sampling from one tertiary cancer hospital and two tertiary general hospitals in Chongqing, China. Patients completed questionnaires on demographics, medical information, Distress thermometer, Perceived Social Support Scale, Posttraumatic Growth Inventory, and Herth Hope Index. Statistical analyses included Pearson’s chi-squared test or Fisher’s exact test for differences in patient characteristics by psychological distress level. Pearson correlation analysis explored relationships among variables. Bootstrapping in structural equation modeling (SEM) evaluated structural paths, and multi-group SEM analysis tested the moderating effect of gender.Results: 43.6% (219/502) of lung cancer patients experience psychological distress. After controlling for cancer stage and distant metastasis, the results suggested that social support had a negative direct effect on psychological distress. In addition, social support could also influence psychological distress via three pathways: (1) the mediating effect of hope, (2) the mediating effect of PTG, and (3) the serial mediating effect of hope and PTG. The indirect effect of the three intermediary paths accounted for 72.7% of the total effect. Gender moderated the effect of social support on PTG (β = − 0.286, P = 0.001).Conclusion: This study found that lung cancer patients exhibit high levels of psychological distress. Social support directly impacts psychological distress and acts through multiple pathways: the mediating effects of hope and PTG, as well as their serial mediation. These findings deepen our understanding of how social support affects psychological distress in lung cancer patients and its underlying mechanisms, providing empirical support for developing interventions to alleviate distress.Keywords: lung cancer, social support, psychological distress, hope, posttraumatic growth, serial mediation model